Koligacje rodzinne Profesora Stanisława Kurnatowskiego - Gucia, Dobrosława; Pihan-Kijasowa, Alicja; Wojtczak, jakub (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
In part one, the family relations of professor Stanisław Kurnatowski are presented as a representative of an old noble family from Wielkopolska with Łodzia as its coat of arms. In the second part of the article, fragments of Prof. Kurnatowski’s memoirs are presented as recorded by the authors during a visit paid to the professor in June 2015. He reminisced about his family’s last four generations (his maternal and paternal ancestors from the landed gentry and relations with numerous families).